Harga Diri Dengan Intensitas Selfie Pada Ibu Rumah Tangga - Uswatun Hasanah; Beti Malia Rahma Hidayati (IDEA: Jurnal Psikologi, 2021)
The purpose of this study is to examine whether there is a relationship between self-esteem and the intensity of selfies in housewives.The hypothesis proposed is that there is a relationship between Self-Esteem and Selfie Intensity. The sample subjects in this research were 40 housewives in Jombang. The sampling methode used in this research is purposive random sampling. Based on the results of Sperman's rho analysis, it was found that the rho index = 0.076 with p value = 0.641 (p > 0.05). It shows that there is no correlation between self-esteem and selfie intensity in housewives. Keywords: Self-Esteem, Selfie Intensity.